Potential applications of assisted reproductive technologies (ART) in reindeer (Rangifer tarandus) - Lindeberg, H.; Nikitkina, E.; Nagy, Sz.; Musidray, A.; Shiryaev, G.; Kumpula, J.; Holand, Ø. (Animal Reproduction Science)
Interest in the use of assisted reproductive technology in reindeer husbandry has gradually increased during the last decades. This article reviews Western and Russian literature on reindeer semen collection, semen cryopreservation and artificial insemination. In addition, literature on the synchronisation of the stage of reindeer oestrous cycle among females, recovery of in vivo embryos, embryo transfer, the production of in vitro-produced embryos and pregnancy diagnosis is reviewed. 2021